Divergent population trends following the cessation of legal grizzly bear hunting in southwestern British Columbia, Canada. (May 2019) - McLellan, Michelle L.; McLellan, Bruce N.; Sollmann, Rahel; Lamb, Clayton T.; Apps, Clayton D.; Wittmer, Heiko U.
Abstract: We conducted DNA capture-recapture monitoring of grizzly bears ( Ursus arctos ) from 5 to 17 years after hunting was stopped in two adjacent but genetically distinct populations in southwestern British Columbia, Canada. We used spatial capture-recapture and non-spatial Pradel robust design modelling to estimate population density, trends, and the demographic components of population change for each population. The larger population had 21.5 bears/1000 km 2 and was growing (λPradel = 1.02 ± 0.02 SE; λsecr = 1.01 ± 4.6 × 10 −5 SE) following the cessation of hunting. The adjacent smaller population had 6.3 bears/1000 km 2 and was likely declining (λPradel = 0.95 ± 0.03 SE; λsecr = 0.98 ± 0.02 SE). Estimates of apparent survival and apparent recruitment indicated that lower recruitment was the dominant factor limiting population growth in the smaller population. Factors limiting reproductive rates and population density could include poor habitat quality, particularly the abundance of high-energy foods, genetic Allee effects due to a long period of population isolation, or demographic effects affecting infanticide rates. The cessation of hunting was insufficient to promote population recovery for the low density, isolated population. Our research highlights the importance of considering mortality thresholds in addition to small population effects and habitat quality when recovering large carnivore populations.